MANAGEMENT OF THE BASIC EDUCATION DATA SYSTEM (DAPODIK) ADMINISTRATION IN TOLIKARA REGENCY: CHALLENGES AND STRATEGIES FOR STRENGTHENING DATA-DRIVEN EDUCATIONAL GOVERNANCE - Simson Wandik; Erni Murniarti (SOSIOEDUKASI, 2026)
Digital transformation in education has encouraged the utilization of information systems as a primary instrument for data-driven educational governance. One of the strategic systems is the Basic Education Data System (Dapodik), which serves as the main source of educational data for planning, implementation, evaluation, and policy-making processes in Indonesia. However, the implementation of Dapodik in remote areas continues to face various challenges that may affect data quality and the effectiveness of educational policies. This article aims to analyze the strategic role of Dapodik in educational governance, identify challenges in managing Dapodik administration in Tolikara Regency, and formulate strategies to strengthen digital-based educational data management. This study employs a literature review method with a descriptive qualitative approach by analyzing scientific publications, government regulations, policy documents, and previous relevant studies. The findings indicate that Dapodik management in remote areas is constrained by limited human resource competencies, inadequate technological infrastructure, weak organizational governance, and the underutilization of data for decision-making processes. Therefore, strengthening strategies are required through capacity building for operators, digital infrastructure development, improved monitoring and evaluation systems, and the cultivation of a data-driven decision-making culture. Strengthening Dapodik management is expected to improve educational governance and support more effective, accurate, and sustainable educational policy formulation.